2018
DOI: 10.3390/ijerph15112519
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasound Imaging Pixel Analysis of the Intrinsic Plantar Muscle Tissue between Hemiparesis and Contralateral Feet in Post-Stroke Patients

Abstract: Quantitative ultrasound imaging of the muscle tissue may be applied in the neurology field, due to B-mode grayscale pixels values could be used as potential biomarkers for disease progression and intervention effects in poststroke patients. Thus, the study aim was to compare and analyze the ultrasound imaging B-mode pixels differences between the intrinsic plantar muscles cross-sectional area (CSA) in hemiparetic and contralateral feet from poststroke patients by means of the Image J software. A case-control d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Major differences were observed in the intervention group compared to the control, but improvements in both could be explained by the increase in training levels and maintenance of physical activity, respectively. Specifically, muscle echointensity has been proposed as a possible biomarker to predict frailty, detecting intramuscular adipose tissue infiltration or "myoesteatosis", as well as identifying intramyocellular lipid droplet characteristics in degenerative conditions such as sarcopenia, neurodegenerative diseases or myopathies [19,23,33,45,46]. Similar findings were reported by previous authors who considered EI a useful parameter in assessing intramuscular content changes with aging; however, no previous studies have researched the differences between pre-frail groups after a multicomponent intervention [24,47,48].…”
Section: Quantitative Ultrasound Imaging For Tissue Echogenicity and Homogeneitymentioning
confidence: 54%
See 2 more Smart Citations
“…Major differences were observed in the intervention group compared to the control, but improvements in both could be explained by the increase in training levels and maintenance of physical activity, respectively. Specifically, muscle echointensity has been proposed as a possible biomarker to predict frailty, detecting intramuscular adipose tissue infiltration or "myoesteatosis", as well as identifying intramyocellular lipid droplet characteristics in degenerative conditions such as sarcopenia, neurodegenerative diseases or myopathies [19,23,33,45,46]. Similar findings were reported by previous authors who considered EI a useful parameter in assessing intramuscular content changes with aging; however, no previous studies have researched the differences between pre-frail groups after a multicomponent intervention [24,47,48].…”
Section: Quantitative Ultrasound Imaging For Tissue Echogenicity and Homogeneitymentioning
confidence: 54%
“…Finally, the echotexture of the tissue was evaluated by quantitative analysis of pixels on the RF at 50% displaying a histogram of the pixels' distribution. Afterwards, EI and EV of the tissue were calculated counting 2500 pixels (50 × 50) in a rectangular range of interest (RF-ROI; Figure 2D) placed in the center of the RF, below its central aponeuroses, in order to reduce the increase in reflection from hiperechogenic connective tissue, at 1 cm deep using the ultrasound devices' scale bar from the lateral side of the extracted images as a reference [20,23,[32][33][34]. Echointensity was registered as the mean value of the ROI histogram while EV was calculated using the previous method described by Ríos et al that uses the standard deviation (SD) and mean value of intensity (EI) in the ROI (EV = SD/EI × 100) [23].…”
Section: Ultrasound Imaging Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a stroke patient with spasticity finds it difficult to control posture, and due to the maintenance of a continuous muscle contraction state, it is difficult to induce proper muscle strength and to perform other movements [15][16][17]. Previous studies reported that spasticity causes morphological changes in muscle thickness in stroke patients [18,19]. Pharmacotherapeutic agents [20], transcutaneous electrical stimulation [21], taping [22], and other therapeutic modalities can be employed to alleviate the intensity of spasticity in stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 Motor functions are more severely affected, and patients have many long-term musculoskeletal disorders. 8,9 The patients' quality of life decreases rapidly due to the reduced possibilities of independent functioning, primarily mobility and self-service related to personal hygiene. 10 This is primarily due to postural instability, which is understood not only as of the maintenance of balance in a standing position but also as the ability to recover balance despite the action of external destabilizing stimuli.…”
Section: Introductionmentioning
confidence: 99%